The Influence of Accounting Knowledge in Moderating Relationship between Understanding and Socialization of Tax Toward MSMEs Tax Compliance - Rahayu, Apriani Kartika; Bawono, Icuk Rangga; Sudibyo, Yudha Aryo (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2020)
This research aims to analyze the understanding and socialization of taxation on tax compliance of MSMEs. This research also aims to analyze the influence of understanding of accounting in moderating the relationship of understanding and socialization of taxation on tax compliance of MSMEs. Samples were determined by the stratified cluster sampling method. The number of respondents is 151 MSMEs owners/managers/actors in sectors of the trade, hotel, and restaurant. This study uses the Structural Equation Model (SEM) to analyze the purposes of this research. Effect size analysis is used to determine how big is the moderation effect from the variable of accounting knowledge. Through path analysis, this research states that taxation understanding and socialization have a significant positive effect on tax compliance of MSMEs. Then, accounting knowledge has a significant and weakening effect on moderating the relationship between taxation understanding and tax compliance of MSMEs. Meanwhile, accounting knowledge has not been proven to moderate the relationship between tax socialization on tax compliance of MSMEs. Penelitian ini bertujuan untuk menganalisis pemahaman dan sosialisasi perpajakan terhadap kepatuhan pajak UMKM. Penelitian ini juga bertujuan untuk menganalisis pengaruh pemahamana akuntansi dalam memoderasi hubungan dari pemahaman dan sosialisasi perpajakan terhadap kepatuhan pajak UMKM. Sampel ditentukan menggunakan metode stratified cluster sampling. Jumlah responden adalah 151 pemilik/manajer/pelaku UMKM yang bergerak pada sektor perdagangan, hotel dan restoran. Penelitian ini menggunakan Structural Equation Model (SEM) untuk menganalisis tujuan penelitian ini. Analisis ukuran efek digunakan untuk menentukan besar pengaruh moderasi dari variabel pemhaman akuntansi. Melalui analisis jalur, hasil penelitian ini menyatakan bahwa pemahaman dan sosialisasi perpajakan berpengaruh positif signifikan terhadap kepatuhan pajak UMKM. Kemudian, pemahaman akuntansi berpengaruh signifikan dan bersifat melemahkan dalam memoderasi hubungan pemahaman perpajakan pada kepatuhan pajak UMKM. Sementara itu, pemahaman akuntansi tidak terbukti hubungan memoderasi hubungan sosialisasi pajak pada kepatuhan pajak UMKM.